2012
DOI: 10.5021/ad.2012.24.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Assessment in Male Patients with Androgenetic Alopecia: Result of a Prospective, Multicenter Study

Abstract: BackgroundAndrogenetic alopecia (AGA) is a common hair loss disease with genetic predisposition among men and women, and it may commence at any age after puberty. It may significantly affect a variety of psychological and social aspects of one's life and the individual's overall quality of life (QoL).ObjectiveThis study aimed to investigate the QoL of AGA patients and discover the factors that can influence the QoL of AGA patients, including previous experience in non-medical hair care, reasons for hospital vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(159 citation statements)
references
References 17 publications
8
147
4
Order By: Relevance
“…Thus as the severity of androgenic alopecia increases among Indian males, the quality of life also deteriorates proportionately due to psychological effects of alopecia on them and the social stigma of aging associated with it. This is supported by studies done by Han et al in South Korea in Asian population and Prinsen et al in Netherlands in Caucasian population where they found significant association between quality of life as assessed by skindex-29 and severity of androgenic alopecia [2,15]. Thus this study can serve as a guideline for male patients with androgenic alopecia in the Indian population.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Thus as the severity of androgenic alopecia increases among Indian males, the quality of life also deteriorates proportionately due to psychological effects of alopecia on them and the social stigma of aging associated with it. This is supported by studies done by Han et al in South Korea in Asian population and Prinsen et al in Netherlands in Caucasian population where they found significant association between quality of life as assessed by skindex-29 and severity of androgenic alopecia [2,15]. Thus this study can serve as a guideline for male patients with androgenic alopecia in the Indian population.…”
Section: Discussionsupporting
confidence: 74%
“…Low confidence and low self-esteem in also seen in majority of patients with androgenic alopecia [6]. Hence, importance needs to be given on how help can be given to these patients in the most reasonable, easily affordable and with better compliance [2].…”
Section: Introductionmentioning
confidence: 99%
“…Han SH et al 19 also showed that function and emotion scales are more severly affected in younger age group as compared to older age group. In a study older patients were more severely afflicted for subscales of functioning, stigmatization and symptoms whereas emotional score was more severely affected in young population.…”
mentioning
confidence: 99%
“…It may significantly affect a variety of psychological and social aspects of one's life and the individual's overall quality of life [1].…”
Section: Introductionmentioning
confidence: 99%